2018
DOI: 10.1108/nfs-02-2018-0062
|View full text |Cite
|
Sign up to set email alerts
|

Fenugreek proteins and their hydrolysates prevent hypercholesterolemia and enhance the HDL antioxidant properties in rats

Abstract: Purpose-This paper aims to investigate the in vivo hypocholesterolemic property of fenugreek proteins (FP), Purafect-fenugreek protein hydrolysate (PFPH) and Esperase-fenugreek protein hydrolysate (EFPH) on high cholesterol (HC)-fed rats. Design/methodology/approach-Rats were randomized into five groups: four were fed for four weeks a hypercholesterolemic diet and the tested products were given by gavage. The fifth group was taken as control (C) receiving the same diet without cholesterol. Findings-Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…A range of concentrations of the avocado extracts (62.5, 125, 250, 500, and 1000 µg/mL) was tested. These concentrations were chosen based on previous work, carried out by our research group, using different plant extracts [19][20][21]. For cytotoxicity screening assays, the cells were seeded in 96-well plates at a density of 4 × 10 3 cells/well.…”
Section: Cell Culture Cell Treatment and Determination Of Citotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…A range of concentrations of the avocado extracts (62.5, 125, 250, 500, and 1000 µg/mL) was tested. These concentrations were chosen based on previous work, carried out by our research group, using different plant extracts [19][20][21]. For cytotoxicity screening assays, the cells were seeded in 96-well plates at a density of 4 × 10 3 cells/well.…”
Section: Cell Culture Cell Treatment and Determination Of Citotoxicitymentioning
confidence: 99%
“…Since previous studies on plant extracts suggested mitochondrial dysfunction and intrinsic apoptosis induction [19][20][21], the mitochondrial membrane potential change was also analyzed in this study. Mitochondria play a key role in the apoptosis induction and are associated with the changes in the mitochondrial membrane permeability.…”
Section: Apoptosis Analysismentioning
confidence: 99%
“…Aromatic, hydrophobic, and positively charged amino acids were similar in both hydrolysates. The detailed amino acids composition of fenugreek protein hydrolysates is reported in Reference [16].…”
Section: Resultsmentioning
confidence: 99%
“…A study undertaken by Chi et al [46] confirmed that peptides with a smaller molecular size, the presence of hydrophobic and aromatic amino acid residues, and the amino acid sequences were the key factors that determine the antioxidant activities of hydrolysates and peptides. Fenugreek protein hydrolysates are rich in hydrophobic and aromatic amino acids [16]. Moreover, as the cells incubated with protein hydrolysates were washed, some peptides may be lost since they are not able to cross the cell membrane due to their big size and polarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation